The Energy Transition of the Transition Economies : An Empirical Analysis - Zhang, Fan (Elsevier, 2013)
The aggregate manufacturing energy intensity of 28 countries in Eastern Europe and Central Asia had declined by 35% during 1998–2008. This study reveals a strong evidence of convergence: less efficient countries improved more rapidly and the cross-country variance in energy productivity narrowed over time. An index decomposition analysis indicates that energy intensities declined largely because of more efficient energy use rather than shifts from energy intensive to less intensive manufacturing activities. Income growth and energy price increases were the main drivers of the convergence. They dominated the impact of trade, which led to specialization in energy intensive industries.